2019
DOI: 10.1101/576405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic evaluation of the design, orientation, and sequence context dependencies of massively parallel reporter assays

Abstract: Massively parallel reporter assays (MPRAs) functionally screen thousands of sequences for regulatory activity in parallel. Although MPRAs have been applied to address diverse questions in gene regulation, there has been no systematic comparison of how differences in experimental design influence findings. Here, we screen a library of 2,440 sequences, representing candidate liver enhancers and controls, in HepG2 cells for regulatory activity using nine different approaches (including conventional episomal, STAR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…We performed 5 technical replicates, including each allele in 5 oligos with different barcodes (10 barcodes per SNP). To maximize the number of assayed SNPs, each allele was only profiled in one direction, since concordance between the two directions has been shown to be high (Klein et al, 2019).…”
Section: Mpra Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed 5 technical replicates, including each allele in 5 oligos with different barcodes (10 barcodes per SNP). To maximize the number of assayed SNPs, each allele was only profiled in one direction, since concordance between the two directions has been shown to be high (Klein et al, 2019).…”
Section: Mpra Design and Methodsmentioning
confidence: 99%
“…For each SNP we include 5 oligos (technical replicates) for each allele. To increase the number of assayed SNPs, each allele was only profiled in one direction as it has been shown that there is high concordance between the two directions (Klein et al, 2019). We synthesized a 95 bp region surrounding each allele.…”
Section: Mpra Design and Quality Controlsmentioning
confidence: 99%
“…Numerous high-throughput sequencing methods identify enhancers using either plasmid or integrated reporter constructs and are collectively known as massively parallel reporter assays (MPRAs). While these assays offer unprecedented throughput for surveying genome function, their technical biases and limitations are a focus of ongoing research and optimization [23][24][25] . For example, most published MPRAs have been limited to short synthetic sequences (50-150 bp), despite the precise size of genomic enhancers remaining unknown 11 .…”
Section: Introductionmentioning
confidence: 99%
“…While the RET SNPs were several hundred kilobases apart, another challenge is with variants in very close proximity, potentially within the same regulatory element. While oligo synthesis is limited in length, MPRA-based assay of such variants spanning up to 700bp is now possible with use of PCR amplification of oligos with uniquely complimentary ends (93). Likewise, 'capture-and-clone' MPRA designs, often using STARR-seq architecture to simplify cloning, fragment genomic DNA or capture e.g.…”
Section: The Utility Of Mpras For Parsing Linked Variationmentioning
confidence: 99%